Mineralogical characterization of clay fraction of Chalan Beel soils of Bangladesh - Islam, ABMS; Hussain, MS (Journal of the Bangladesh Agricultural University, 2010)
Top soils of four different series viz Jaonia (Typic Haplaquept), Halti (Typic Haplaquept), Taras (Aeric Haplaquept) and Digli (Typic Haplaquept) developed on Atrai river alluvium were studied to investigate the clay mineralogical composition. X-ray diffraction technique was employed to identify and quantify the minerals. The XRD patterns were obtained with Ni-filter Cu kα - radiation at a scanning speed of 2º2θ min and the amount of minerals was estimated by XRD peak intensities at parallel powder mount. Mica was the dominant clay mineral (33 - 51%) in all soils, followed by quartz (13 -19%). The kaolinite contents were small (8 - 10%) over the soils. The occurrence of vermiculite in the Digli and Taras soils (9 and 7% respectively) indicates a considerable transformation of mica. There is very little or no smectite minerals in the soils which might be due to poor parent material and disappearance of smectite from the top soils. Appreciable amount of primary minerals like quartz and feldspars have also been observed in the clay fraction of the soils. Keywords: Clay minerals; Chalan beel; X-ray diffraction DOI: 10.3329/jbau.v6i2.4819 J. Bangladesh Agril. Univ. 6(2): 253-260, 2008